Global distribution and vertical patterns of a prymnesiophyte–cyanobacteria obligate symbiosis - Cabello, Ana M (ISME J, 2016)
A marine symbiosis has been recently discovered between prymnesiophyte species and the unicellular diazotrophic cyanobacterium UCYN-A. At least two different UCYN-A phylotypes exist, the clade UCYN-A1 in symbiosis with an uncultured small prymnesiophyte and the clade UCYN-A2 in symbiosis with the larger Braarudosphaera bigelowii. We targeted the prymnesiophyte–UCYN-A1 symbiosis by double CARD-FISH (catalyzed reporter deposition-fluorescence in situ hybridization) and analyzed its abundance in surface samples from the MALASPINA circumnavigation expedition. Our use of a specific probe for the prymnesiophyte partner allowed us to verify that this algal species virtually always carried the UCYN-A symbiont, indicating that the association was also obligate for the host. The prymnesiophyte–UCYN-A1 symbiosis was detected in all ocean basins, displaying a patchy distribution with abundances (up to 500 cells ml(−1)) that could vary orders of magnitude. Additional vertical profiles taken at the NE Atlantic showed that this symbiosis occupied the upper water column and disappeared towards the Deep Chlorophyll Maximum, where the biomass of the prymnesiophyte assemblage peaked. Moreover, sequences of both prymnesiophyte partners were searched within a large 18S rDNA metabarcoding data set from the Tara-Oceans expedition around the world. This sequence-based analysis supported the patchy distribution of the UCYN-A1 host observed by CARD-FISH and highlighted an unexpected homogeneous distribution (at low relative abundance) of B. bigelowii in the open ocean. Our results demonstrate that partners are always in symbiosis in nature and show contrasted ecological patterns of the two related lineages.